Cerium dioxide-based solid solution current response catalyst as well as preparation method and application thereof

By introducing a second metal into ceria to form a solid solution catalyst, the problem of insufficient redox capacity of ceria is solved, and the effect of efficiently cracking light alkanes under mild conditions is achieved.

CN119750631AActive Publication Date: 2025-04-04HUIZHOU INSTITUTE OF GREEN ENERGY & ADVANCED MATERIALS +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411885492.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, the redox capacity of ceria is insufficient, resulting in poor catalytic cracking performance, making it difficult to efficiently crack light alkanes under mild conditions to prepare low-carbon olefins.

Method used

By introducing a second metal into ceria, a ceria-based solid solution current response catalyst of CexM1-xO2 (0

Benefits of technology

It has achieved a significant increase in the conversion rate of light alkanes and the selectivity of low-carbon olefins under mild conditions, reduced the reaction temperature, improved catalytic activity, inhibited the occurrence of side reactions, and achieved green and low-carbon preparation of low-carbon olefins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a cerium dioxide-based solid solution current response catalyst and a preparation method and application thereof, the composition of the catalyst is characterized in that the catalyst is CexM1-xO2 (x is more than 0 and less than 1) (M is Al, Mn, Fe, Co, Zn, Zr, In or Sm), and the catalyst can be prepared by a co-precipitation method (CP) or a sol-gel method (Sol-Gel). According to the present invention, with the cerium dioxide-based solid solution as the current response catalyst, the low-carbon olefin preparation through the light alkane directional cracking under the mild condition (300-450 DEG C) can be achieved, and compared with the electric field-free condition under the same condition, the light alkane conversion rate can be improved by 15-60%, and the low-carbon olefin selectivity can be improved by 30-60%. The light hydrocarbon cracking process based on catalysis of the cerium dioxide-based solid solution enhanced by the electric field has the advantages of mild reaction conditions, high energy utilization rate and the like, and the problems of high temperature (650-680 DEG C) and high energy consumption in the traditional light hydrocarbon catalytic cracking process are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petrochemical industry, and relates to a current responsive catalyst and a preparation method and application thereof, and in particular to a cerium dioxide-based solid solution current responsive catalyst and a preparation method and application thereof. Background Art

[0002] With the high-quality development of my country's economy, the petrochemical industry, as one of the country's pillar industries, is also in a stage of continuous change and development. Among them, the production capacity and market demand of low-carbon olefins such as ethylene and propylene continue to grow every year. It is estimated that by 2030, this demand will reach 385 million tons. The more mature process for the industrial preparation of ethylene and propylene is naphtha steam cracking. The reaction temperature is usually higher than 800°C. It is a typical high-energy consumption and high-carbon emission process. Carbon emissions account for ~40% of the entire petrochemical industry, and the product distribution is not easy to control.

[0003] Driven by the "dual carbon" goal, it is imperative to achieve green and low-carbon upgrading of the petrochemical industry. "Green electricity" energy supply can use clean and renewable electricity to replace traditional fossil fuels, providing efficient and controllable energy for the petrochemical process. At the same time, it can also regulate the structure and reaction behavior of petroleum molecules and catalytic materials through the action of electric fields, and realize the directional conversion of petroleum molecules into high-value-added chemicals.

[0004] The effect of an external electric field powered by "green electricity" is expected to achieve efficient cracking of light hydrocarbons under mild conditions. The key lies in the development of high-performance current-responsive catalysts. Current-responsive catalysts are a type of catalytic material with suitable conductivity that can generate current under applied electric field conditions. Molecular sieves are suitable catalysts for catalytic cracking processes, but molecular sieve materials have poor electrical conductivity. Solid solutions are a type of material with good electrical conductivity. CN118910661A discloses an integrated solid solution electrode obtained by solvothermal reaction of ruthenium and manganese. The formation of ruthenium-manganese solid solution is beneficial to improving the overall stability of the electrode. CN118756095A discloses a Ti2(Al2O3) prepared by high-power pulsed magnetron sputtering technology. 1-x Sn x )C solid solution, which can exist stably in an acidic environment and has excellent conductive properties.

[0005] The present invention improves the electrical conductivity and redox ability of the obtained material by introducing a second metal into ceria, thereby solving the problem of poor catalytic cracking performance caused by insufficient redox ability of ceria, and achieving efficient cracking of light alkanes to produce low-carbon olefins under mild conditions. Summary of the invention

[0006] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.

[0007] The present invention provides a ceria-based solid solution current-responsive catalyst and a preparation method thereof, which has the advantage of greatly improving the conversion rate of light alkanes and the selectivity of low-carbon olefins under mild conditions, thereby realizing the green preparation of low-carbon olefins.

[0008] The technical scheme adopted in this application is as follows: The composition characteristics of the cerium dioxide-based solid solution current response catalyst developed to enhance the cracking of light alkanes to produce more low-carbon olefins under mild conditions are Ce x M 1-x O2 (0<x<1) (M is Al, Mn, Fe, Co, Zn, Zr, In or Sm), preparation methods include: coprecipitation method (CP) and sol-gel method (Sol-Gel).

[0009] The coprecipitation method (CP) for preparing the ceria-based solid solution catalyst comprises the following steps:

[0010] (1) Add a certain amount of cerium nitrate into an appropriate amount of deionized water and stir at room temperature until it is completely dissolved;

[0011] (2) adding a certain amount of the second metal precursor into an appropriate amount of deionized water and stirring at room temperature until the mixture is completely dissolved;

[0012] (3) pouring (2) into (1), stirring evenly, adding a certain amount of precipitant, stirring continuously at room temperature, and allowing to stand after stirring; and

[0013] (4) The static solution is centrifuged, washed and dried several times to obtain a preliminary solid product, which is then calcined to obtain a ceria-based solid solution catalyst CP-Ce x M 1-x O2(0<x<1)(M is Al, Mn, Fe, Co, Zn, Zr, In or Sm).

[0014] In step (2) of the above method, the second metal precursor is one of aluminum nitrate, manganese nitrate, iron nitrate, cobalt nitrate, zinc nitrate, zirconium nitrate, indium nitrate and samarium nitrate.

[0015] The precipitant in step (3) of the above method is one or more of ammonia water, ammonium carbonate or ammonium bicarbonate. After adding the precipitant, the pH of the solution is adjusted to 7-11, and the standing time is 0.5-48 hours; more preferably, after adding the precipitant, the pH of the solution is adjusted to 8-10, and the standing time is 0.5-36 hours.

[0016] In step (4) of the above method, the drying temperature is 80-150°C, the drying time is 6-24h, the roasting temperature is 400-700°C, the roasting time is 5-72h, and the heating rate is 2-10°C / min; more preferably, the drying temperature is 100-120°C, the drying time is 8-12h, the roasting temperature is 500-650°C, the roasting time is 5-48h, and the heating rate is 2-5°C / min.

[0017] The sol-gel method for preparing the ceria-based solid solution catalyst comprises the following steps:

[0018] (a) adding a certain amount of cerium nitrate into an appropriate amount of deionized water and stirring at room temperature until it is completely dissolved;

[0019] (b) adding a certain amount of the second metal precursor into an appropriate amount of deionized water and stirring at room temperature until the second metal precursor is completely dissolved;

[0020] (c) pouring (b) into (a), stirring evenly, adding a certain amount of complexing agent, and continuously stirring at a certain temperature until the solution becomes a light yellow gel; and

[0021] (d) drying the pale yellow gel-like substance to obtain a preliminary solid product, and calcining the solid solution current-responsive catalyst Sol-Gel-CeO2. x M 1-x O2(0<x<1)(M is Al, Mn, Fe, Co, Zn, Zr, In or Sm).

[0022] In step (b) of the above method, the second metal precursor is one of aluminum nitrate, manganese nitrate, iron nitrate, cobalt nitrate, zinc nitrate, zirconium nitrate, indium nitrate and samarium nitrate.

[0023] In step (c) of the above method, the complexing agent is citric acid, the molar ratio of the added citric acid to the total metal is (1-3):1, and the stirring temperature is 50-100°C; more preferably, the molar ratio of the added citric acid to the total metal is (1-2.5):1, and the stirring temperature is 60-90°C.

[0024] In step (d) of the above method, the drying temperature is 80-150°C, the drying time is 6-24h, the roasting temperature is 400-700°C, the roasting time is 5-72h, and the heating rate is 2-10°C / min; more preferably, the drying temperature is 100-120°C, the drying time is 8-12h, the roasting temperature is 500-650°C, the roasting time is 5-48h, and the heating rate is 2-5°C / min.

[0025] The present invention also provides an application of a ceria-based solid solution current-responsive catalyst in catalyzing the cracking of light alkanes to produce low-carbon olefins. The application process mainly includes the following steps:

[0026] (i) pressing the prepared ceria-based solid solution current-responsive catalyst into tablets, sieving to 20-40 mesh, and taking 1.85 g of the catalyst and loading it into a fixed bed reactor equipped with electrodes;

[0027] (ii) In a N2 atmosphere, the reactor was raised to the target temperature, a direct current was applied, and the temperature was stabilized for 2 h; and

[0028] (iii) introducing a light alkane feedstock to start the reaction, and using gas chromatography to analyze the product composition online.

[0029] In the application of the above-mentioned cerium dioxide-based solid solution current-responsive catalyst, the catalytic cracking of light alkanes to produce low-carbon olefins uses chain length C4~C10 alkanes as raw materials and N2 as carrier gas, wherein the space velocity of the light alkanes is 10~80mmol / (g·h), the N2 flow rate is 5~60mL / min, the cracking reaction temperature is 300~450℃, the DC voltage is 0~1000V, the current is 0~3A, and the power is 0~50W; more preferably, the space velocity of the light alkanes is 20~40mmol / (g·h), the N2 flow rate is 10~50mL / min, the DC voltage is 0~800V, the current is 0~2A, and the power is 0~30W.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The catalytic material prepared by the cerium dioxide-based catalyst synthesis method provided by the present invention is doped with a second metal element M without destroying the cubic fluorite structure of CeO2, where M is Al, Mn, Fe, Co, Zn, Zr, In or Sm, thereby enhancing the redox ability of CeO2 and having a current response characteristic under the action of a direct current electric field; and

[0032] (2) The cerium dioxide-based solid solution current-responsive catalyst provided by the present invention is applied to the catalytic cracking of light alkanes to produce low-carbon olefins. Under thermoelectric coupling conditions, the reaction temperature is reduced, the catalytic activity is improved, the occurrence of side reactions is suppressed, the selectivity of low-carbon olefins is improved, and the green and low-carbon preparation of low-carbon olefins is achieved.

[0033] Other aspects will be apparent upon reading and understanding the detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] none DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0036] Example 1

[0037] Preparation of Ce-Al Solid Solution Current-Response Catalyst CP-Ce by Coprecipitation x Al 1-x O2(0<x<1)

[0038] (1) Add a certain amount of cerium nitrate into an appropriate amount of deionized water and stir at room temperature until it is completely dissolved;

[0039] (2) Add a certain amount of aluminum nitrate to an appropriate amount of deionized water and stir at room temperature until it is completely dissolved;

[0040] (3) Pour (2) into (1), stir evenly, add a certain amount of ammonia water, adjust the solution pH to 10, continue stirring at room temperature, and after stirring, let stand for 24 hours; and

[0041] (4) The static solution was centrifuged and washed several times, and dried at 110°C for 10 h to obtain a preliminary solid product, and the solid product was calcined at 600°C for 8 h to obtain a cerium aluminum solid solution current response catalyst CP-Ce x Al 1-x O2(0<x<1).

[0042] Example 2

[0043] The cerium-manganese solid solution current response catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Mn 1-x O2 (0<x<1), except that the second metal precursor in step (2) is manganese nitrate.

[0044] Example 3

[0045] The ferrocerium solid solution current response catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Fe 1-x O2 (0<x<1), except that the second metal precursor in step (2) is ferric nitrate.

[0046] Example 4

[0047] The cerium-cobalt solid solution current responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Co 1-x O2 (0<x<1), except that the second metal precursor in step (2) is cobalt nitrate.

[0048] Example 5

[0049] The cerium zinc solid solution current response catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Zn 1-x O2 (0<x<1), except that the second metal precursor in step (2) is zinc nitrate.

[0050] Example 6

[0051] The cerium-zirconium solid solution current responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Zr 1-x O2 (0<x<1), except that the second metal precursor in step (2) is zirconium nitrate.

[0052] Example 7

[0053] The cerium-indium solid solution current response catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x In 1-x O2 (0<x<1), except that the second metal precursor in step (2) is indium nitrate.

[0054] Example 8

[0055] The cerium-samarium solid solution current response catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Sm 1-x O2 (0<x<1), except that the second metal precursor in step (2) is samarium nitrate.

[0056] Example 9

[0057] Preparation of Ce-Al Solid Solution Current-Response Catalyst Sol-Gel-Ce by Sol-Gel Method x Al 1-x O2(0<x<1)

[0058] (a) adding a certain amount of cerium nitrate into an appropriate amount of deionized water and stirring at room temperature until it is completely dissolved;

[0059] (b) adding a certain amount of aluminum nitrate to an appropriate amount of deionized water and stirring at room temperature until it is completely dissolved;

[0060] (c) pouring (b) into (a), stirring evenly, and adding a certain amount of citric acid, the molar ratio of citric acid to total metal is 2:1, and stirring continuously at 70° C. until the solution becomes a light yellow gel; and

[0061] (d) Drying the yellow gel-like substance at 110°C for 10 h to obtain a preliminary solid product, and calcining the solid product at 600°C for 8 h to obtain a cerium-aluminum solid solution current responsive catalyst Sol-Gel-Ce x Al 1-x O2(0<x<1).

[0062] Example 10

[0063] The cerium-manganese solid solution current response catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Mn 1-x O2 (0<x<1), except that the second metal precursor in step (b) is manganese nitrate.

[0064] Embodiment 11

[0065] The ferrocerium solid solution current response catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Fe 1-x O2 (0<x<1), except that the second metal precursor in step (b) is ferric nitrate.

[0066] Example 12

[0067] The cerium-cobalt solid solution current response catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Co 1-x O2 (0<x<1), except that the second metal precursor in step (b) is cobalt nitrate.

[0068] Embodiment 13

[0069] The cerium zinc solid solution current response catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Zn 1-x O2 (0<x<1), except that the second metal precursor in step (b) is zinc nitrate.

[0070] Embodiment 14

[0071] The cerium-zirconium solid solution current responsive catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Zr 1-x O2 (0<x<1), except that the second metal precursor in step (b) is zirconium nitrate.

[0072] Embodiment 15

[0073] The cerium-indium solid solution current response catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. xIn 1-x O2 (0<x<1), except that the second metal precursor in step (b) is indium nitrate.

[0074] Example 16

[0075] The cerium-samarium solid solution current response catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Sm 1-x O2 (0<x<1), except that the second metal precursor in step (b) is samarium nitrate.

[0076] Application Examples

[0077] The series of ceria-based solid solution current-responsive catalysts obtained in Examples 1-16 were used to catalyze the cracking of light alkanes. The evaluation device used was a micro-electrode fixed-bed reactor. The specific process was as follows:

[0078] (i) pressing the prepared ceria-based solid solution current-responsive catalyst powder into tablets, sieving to 20-40 mesh, and taking 1.85 g of the catalyst into a micro-electrode fixed-bed reactor;

[0079] (ii) controlling the flow rate of carrier gas N2 to 40.0 mL / min, heating the reactor to a set temperature in a N2 atmosphere, applying direct current (0 / 8 W, 0 W represents no electric field, 8 W represents the power under an applied electric field), and stabilizing for 2 h; and

[0080] (iii) A light alkane feedstock was introduced to start the reaction, wherein the light alkane space velocity was 40 mmol / (g·h). The product composition was analyzed online by gas chromatography, with sampling once every 1 hour. The results in the table are average data within 3 to 5 hours of reaction time.

[0081] The conversion rate and the selectivity of the main products are shown in Table 1 and Table 2. (In the table, "triene" includes ethylene, propylene and butene; "BTX" includes benzene, toluene and xylene)

[0082] Table 1. Performance of the cerium dioxide-based solid solution current response catalyst prepared in the example under the condition of electric field and without electric field for cracking n-hexane

[0083]

[0084] Note: 0W represents no electric field, 8W represents the power under applied electric field

[0085] Table 2. Performance of the cerium dioxide-based solid solution current response catalyst prepared in the example under the condition of electric field and without electric field for cracking n-octane

[0086]

[0087] Note: 0W represents no electric field, and 8W represents the power under applied electric field.

Claims

1. A ceria-based solid solution current-responsive catalyst, characterized in that: The ceria-based solid solution current responsive catalyst is Ce x M 1-x O2(0<x<1).

2. The ceria-based solid solution current-responsive catalyst according to claim 1, characterized in that: M is Al, Mn, Fe, Co, Zn, Zr, In or Sm.

3. A method for preparing the ceria-based solid solution current-responsive catalyst according to any one of claims 1 to 2, characterized in that: The metal nitrate is used as a precursor by coprecipitation (CP) or sol-gel method (Sol-Gel) to prepare the product, wherein the coprecipitation (CP) preparation steps include: (1) Add a certain amount of cerium nitrate into an appropriate amount of deionized water and stir at room temperature until it is completely dissolved; (2) adding a certain amount of the second metal precursor into an appropriate amount of deionized water and stirring at room temperature until the mixture is completely dissolved; (3) pouring (2) into (1), stirring evenly, adding a certain amount of precipitant, stirring continuously at room temperature, and allowing to stand after stirring; and (4) The static solution is centrifuged, washed and dried several times to obtain a preliminary solid product, which is then calcined to obtain a ceria-based solid solution catalyst CP-Ce x M 1-x O2(0<x<1)(M is Al, Mn, Fe, Co, Zn, Zr, In or Sm). The preparation steps of the sol-gel method include: (a) adding a certain amount of cerium nitrate into an appropriate amount of deionized water and stirring at room temperature until it is completely dissolved; (b) adding a certain amount of the second metal precursor into an appropriate amount of deionized water and stirring at room temperature until the second metal precursor is completely dissolved; (c) pouring (b) into (a), stirring evenly, adding a certain amount of complexing agent, and continuously stirring at a certain temperature until the solution becomes a light yellow gel; and (d) drying the yellow gel-like substance to obtain a preliminary solid product, and calcining the solid solution current-responsive catalyst Sol-Gel-CeO2. x M 1-x O2(0<x<1)(M is Al, Mn, Fe, Co, Zn, Zr, In or Sm).

4. The method for preparing the ceria-based solid solution current-responsive catalyst according to claim 3, characterized in that: The precipitant is one or more of ammonia water, ammonium carbonate or ammonium bicarbonate. After adding the precipitant, the solution pH is adjusted to 7-11.

5. The method for preparing the ceria-based solid solution current-responsive catalyst according to claim 3, characterized in that: The complexing agent is citric acid, and the molar ratio of the added citric acid to the total metal is (1-3):

1.

6. The method for preparing the ceria-based solid solution current-responsive catalyst according to claim 3, characterized in that: The second metal precursor is one of aluminum nitrate, manganese nitrate, iron nitrate, cobalt nitrate, zinc nitrate, zirconium nitrate, indium nitrate, and samarium nitrate.

7. The method for preparing the ceria-based solid solution current-responsive catalyst according to claim 3, characterized in that: The drying temperature is 100-120°C, the drying time is 8-12h, the roasting temperature is 500-650°C, the roasting time is 5-48h, and the heating rate is 2-5°C / min.

8. Use of the ceria-based solid solution current-responsive catalyst according to any one of claims 1 to 2 in catalyzing the cracking of light alkanes to produce low-carbon olefins.

9. The use according to claim 8, characterized in that: In the thermoelectric coupled catalytic light alkane cracking process, direct current is used, with a voltage of 0 to 1000 V, a current of 0 to 3 A, and a power of 0 to 50 W.

10. The use according to claim 8, characterized in that: The catalytic cracking temperature of the light alkane is 300-450° C., and the light alkane is an alkane with a chain length of C4-C10.

Citation Information

Patent Citations

  • Conductive corrosion-resistant solid solution MAX phase composite coating as well as preparation method and application thereof

    CN118756095A

  • Cerium zirconium aluminum composite oxides sosoloid with a mesopore structure and method for preparing the same

    CN101112683A

  • Preparation method of iron-doped cerium-base solid solution flue gas denitrification catalyst

    CN107552059A

  • Cerium-based solid solution and preparation method and application thereof

    CN111569892A

  • Cerium-samarium solid solution nickel-based catalyst for hydrogen production by autothermal reforming of acetic acid

    CN112844397A